Simulation modelling for evaluating performance of commuter system with Arena - Seong, Kiem Low; Choong, Yeun Liong (Penerbit Universiti Kebangsaan Malaysia, 2015)
Capital investment on upgrading commuter transportation system may be ineffective if demand of passengers towards commuter is not accounted for. Hence, simulation study is suggested to study the commuter system performance. The system is evaluated from the aspects of waiting time of passengers and number of cases of passengers being left out at the stations. Input data such as arrival time of commuter, arrival process of passengers, capacity of coaches, proportion of passengers to certain destinations, and dwelling time of commuter at stations were collected, modelled, validated and used as input to the simulation model developed using Arena. The developed model is used to generate data related to the performance of the system. An example on application of the model in comparing performance of two classes of commuter is discussed.